2012
DOI: 10.1371/journal.pone.0047497
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pre-mRNA Splicing by a Synthetic Blom7α-Interacting Small RNA

Abstract: Originally the novel protein Blom7α was identified as novel pre-mRNA splicing factor that interacts with SNEVPrp19/Pso4, an essential protein involved in extension of human endothelial cell life span, DNA damage repair, the ubiquitin-proteasome system, and pre-mRNA splicing. Blom7α belongs to the heteronuclear ribonucleoprotein K homology (KH) protein family, displaying 2 KH domains, a well conserved and widespread RNA-binding motif. In order to identify specific sequence binding motifs, we here used Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The RNA-binding protein KHDC4 that affects both 5′ and 3′ splice site selection is also part of the NTC, where it associates with PRPF19 [ 348 ]. Using a Systematic Evolution of Ligands by EXponential enrichment (SELEX) approach with recombinant KHDC4 or its conserved RNA binding domain as bait, an RNA-aptamer was identified that specifically binds to KHDC4 and inhibits splicing in vitro, as demonstrated by the accumulation of synthetic pre-mRNA and a slight inhibition of spliceosome assembly [ 349 ]. Presumably, the aptamer inhibits binding of KHDC4 to its target sequence on the pre-mRNA, thereby preventing proper positioning of the NTC and activation of the catalytic site.…”
Section: Therapeutic Targeting Of Dysregulated Mrna Splicing In Cancermentioning
confidence: 99%
“…The RNA-binding protein KHDC4 that affects both 5′ and 3′ splice site selection is also part of the NTC, where it associates with PRPF19 [ 348 ]. Using a Systematic Evolution of Ligands by EXponential enrichment (SELEX) approach with recombinant KHDC4 or its conserved RNA binding domain as bait, an RNA-aptamer was identified that specifically binds to KHDC4 and inhibits splicing in vitro, as demonstrated by the accumulation of synthetic pre-mRNA and a slight inhibition of spliceosome assembly [ 349 ]. Presumably, the aptamer inhibits binding of KHDC4 to its target sequence on the pre-mRNA, thereby preventing proper positioning of the NTC and activation of the catalytic site.…”
Section: Therapeutic Targeting Of Dysregulated Mrna Splicing In Cancermentioning
confidence: 99%